Influences of Environmental Factors on Tree Distribution of Lower Montane Evergreen Forest at Doi Sutep-Pui National Park, Chiang Mai Province - Marod, Dokrak; Sangkaew, Sarawood; Panmongkol, Aumporn; Jingjai, Atchara (วารสารวนศาสตร์ไทย, 2022)
The influences of environmental factors on tree distribution of lower montane evergreen forest were carried out at Doi Sutep-Pui National Park, Chiang Mai province during October 2012. The objective aimed to clarify the principal environmental factors on tree distribution. Temporary plots, 20 × 50 m, were established based on altitudinal gradient from 900 to 1,600 meter above mean sea level, total 63 plots. All trees with diameter at breast height over than 4.5 cm were measured and identified, in addition, soil samples were collected in every plot. The result showed that the number of 299 tree species in 181 genera and 87 families were found. Tree density was 102.82 trees/ 0.1 ha and basal area was 174.11 m2. The dominance trees from importance value index, IVI, were Castanopsis acuminatissima, Schima wallichii, Castanopsis armata, Pinus kesiya, Helicia nilagirica and Styrax apricus with IVI of 30.28, 16.07, 13.02, 11.06, 7.41 and 7.07 %, respectively. The ordination analysis showed that the environmental factors to determine the distribution of Oaks with Pine stand was high altitude. Soil properties especially percentage of clay were determined tree distribution of montane evergreen forest and the most distributed species were Castanopsis acuminatissima, Castanopsis tribuloides, Styrax benzoides, Eurya acuminata var. acuminata, Magnolia baillonii and Schima wallichii etc. Thus, reforestation of degraded montane evergreen forest should be concerned these species for reducing the succesional period into the climax stage. Keywords: ecological niche, montane evergreen forest, Doi Sutep-Pui, tree distribution, reforestation